2004
DOI: 10.1161/01.cir.0000145160.04084.ac
|View full text |Cite
|
Sign up to set email alerts
|

Role of Myocardial Neuronal Nitric Oxide Synthase–Derived Nitric Oxide in β-Adrenergic Hyporesponsiveness After Myocardial Infarction–Induced Heart Failure in Rat

Abstract: Background-An emerging concept is that a neuronal isoform of nitric oxide synthase (NOS1) may regulate myocardial contractility. However, a role for NOS1-derived nitric oxide (NO) in heart failure (HF) has not been defined. Methods and Results-Using a model of myocardial infarction-induced HF, we demonstrated that cardiac NOS1 expression and activity increased in HF rats (PϽ0.05 and PϽ0.001 versus shams, respectively). This was associated with translocation of NOS1 from the ryanodine receptor to the sarcolemma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
149
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(165 citation statements)
references
References 29 publications
13
149
3
Order By: Relevance
“…Dawson et al 12 demonstrated that nNOS protects against adverse postinfarction remodeling and that infarcted nNOS Ϫ/Ϫ mice responded to dobutamine with a significant decrease in LV systolic function. Of note, and contrary to the findings of Dawson, Bendall et al 13 found an increase in ␤-AR response after preferential nNOS inhibition in infarcted rats. They initially described an upregulation of cardiomyocyte nNOS.…”
contrasting
confidence: 59%
See 2 more Smart Citations
“…Dawson et al 12 demonstrated that nNOS protects against adverse postinfarction remodeling and that infarcted nNOS Ϫ/Ϫ mice responded to dobutamine with a significant decrease in LV systolic function. Of note, and contrary to the findings of Dawson, Bendall et al 13 found an increase in ␤-AR response after preferential nNOS inhibition in infarcted rats. They initially described an upregulation of cardiomyocyte nNOS.…”
contrasting
confidence: 59%
“…Several studies demonstrated a protective role of nNOS in myocardial infarction 12,13,32 or in ischemia/reperfusion injury. 21 The reason for these favorable results may not only be overexpression or (more physiologically) upregulation, but the translocation of nNOS to the plasmamembrane.…”
Section: Nnos and Inotropic Reservementioning
confidence: 99%
See 1 more Smart Citation
“…7). In light of these and other recent data (1,2,15), it appears likely that nNOS molecules in other subcellular compartments (i.e. sarcoplasmic reticulum and mitochondria) also fulfill highly specialized and spatially restricted functions.…”
Section: Discussionsupporting
confidence: 51%
“…In myocardial cells, nNOS has been localized to the sarcolemma (13), sarcoplasmic reticulum (2), and mitochondria (14), and translocation between compartments has been demonstrated (15). It has been speculated that these various localizations provide specificity to NO signaling, but the exact mechanisms have yet to be elucidated.…”
Section: Phospholamban (Plb) Phosphorylation As Well As Sermentioning
confidence: 99%